Optimization of an urban transport system on the condition of different goals of municipal authorities, operators and passengers - Koryagin, Mark; Katargin, Vladimir (Transport, 2016)
A control system of urban passenger transport is considered. The system participants are a passenger flow, a transport operator and municipal authorities. The participants’ strategies include a travel mode choice, a frequency of public transport service, and a road capacity. Objective functions are transport costs, public transport profit, road costs, and travel time. The passenger flow heterogeneity is based on the value of time that has an exponential distribution. The total costs of passenger flow depend on the probability of the travel mode choice. The dependence between travel time, roads capacity, and traffic is based on Greenshields model. The authorities’ objective consists of travel time and road costs, which can be changed by the road capacity. The game theoretic approach is applied to describe the control system. The existence of Nash equilibrium for coalition-free games for two (the passenger flow and the authorities and three (with addition of public transport) players is proved. The characteristics of urban passenger transport were studied based on a numerical example.